On the transformation of regional food systems: From autochthonous to those generated by globalization - Svetlana Kornekova (European Journal of Geography)
Attention is focused on the historical transformation of regional food systems. The latter are interpreted as diversified, regionally defined systems of production, transportation, consumption, as well as aesthetic and spiritual perception of food products based on the use of resources, both of local origin and those attracted from outside. The general approaches to understanding the evolution of regional food systems are considered without specifying the past and present pictures of the differentiated food space. An attempt is made to find the connection of spatial food systems with the "pyramid of needs" by A. Maslow. A special role in the spatial transformation of the food sector is assigned to the process of globalization and, in particular, the strengthening of the hegemony of agrarian transnational corporations, strengthening their influence on the dynamics and structure of production, as well as on food consumption. The connection of the global expansion of food trade networks with the evolution of national cuisines, which are a specific subsystem of the world's food systems, as well as with the so-called "cultural sovereignty" of countries, is noted. It is concluded that it is important to study the sustainable dependencies of regional food systems, manifested in various socioeconomic conditions